C4B null alleles are not associated with genetic polymorphisms in the adjacent gene CYP21A2 in autism - Odell J Dennis; Odell Daniel W; Sweeten Thayne L; Torres Anthony R (BMC, 2008)
Abstract Background Research indicates that the etiology of autism has a strong genetic component, yet so far the search for genes that contribute to the disorder, including several whole genome scans, has led to few consistent findings. However, three studies indicate that the complement C4B gene null allele (i.e. the missing or nonfunctional C4B gene) is significantly more frequent in individuals with autism. Due to the close proximity of the CYP21A2 gene to the C4B locus (3 kb) it was decided to examine samples from autistic subjects, including many with known C4B null alleles for common CYP21A2 mutations. Methods Samples from subjects diagnosed with autism and non-autistic controls (controls) previously typed for C4B null alleles were studied. Allele specific polymerase chain reaction (PCR) methods were used to determine 8 of the most common CYP21A2 genetic mutations, known to completely or partially inhibit 21-hydroxylase, the enzyme encoded by the CYP21A2 gene. Results Although the combined autism and control study subjects had 50 C4B null alleles only 15 CYP21A2 mutations were detected in over 2250 genotypes. Eight mutations were detected in the autistic samples and 7 in the controls. The frequency of CYP21A2 mutations was similar between the autism and control samples. Only one individual (autistic) carried a chromosome containing both C4B null allele and CYP21A2 mutations.